PENGARUH PRICE FAIRNESS, PERCEIVED RISK DAN PERCEIVED VALUE PADA REPURCHASE INTENTION GEN Z DI BALI - Tirtayani, I Gusti Ayu; Aghivirwiati, Gusti Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.01.TAHUN.2024DO - 10.24843/EEB.2024.v13.i01.p04, 2024)
This research investigates the impact of collaboration between TikTok and Tokopedia on repurchase intention among generation Z in Bali. The variables that are focused on are perceived price fairness, perceived value, perceived risk, and repurchase intention. The analysis was carried out using the Structural Equation Modeling method using WarpPLS with a sample of 190 respondents. The findings show that there is a significant relationship between perceived price fairness, perceived value, and perceived risk on repurchase intention. The results of the analysis show that perceptions of fair prices, product or service value, and perceived risk have an important role in shaping Generation Z's desire to make repeat purchases. The implications of this research highlight the importance of marketing strategies that focus on increasing the perception of fair prices, the value provided to consumers, and managing perceived risks to strengthen consumer loyalty in the context of collaboration between TikTok and Tokopedia in the Bali market. This research contributes to understanding consumer purchasing behavior, especially generation Z, in the era of digital platform collaboration.